Elastyczność przedsiębiorstwa i jej konsekwencje dla systemu społecznego - Cierniak-Emerych, Anna; Pietroń-Pyszczek, Agata (The Enterprise's Flexibility and Its Consequences for the Social System, 2008)
The paper examines circumstances that stimulate employers to introduce the policy of flexibility in enterprise. The authors postulate that employers' aim to introduce flexibility in employment should be examined not only in terms of opportunities, but also risks. The risk involved is mainly associated with limited receptivity of the employer towards the issue of employment security, with resulting problems of organizational trust, decreased loyalty of employees and other consequences that affect company operation. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 34, s. 108-116